Odpowiedzi

2010-02-27T18:50:28+01:00
6+(-4)+(-10)=-8
-4-(-9)-3= 2
-16+7-28= -37
4,3-7,4+1,1= -2
(-6,2)+1,6-(-2,3)= -2,3
7,8-5,4-12,1= -10,3
1(jedna cała)1/3=2/9+1/6= 23/18
1(jedna cała)1/8-2(całe)1/4-(-1/2)= -1/8

Najlepsza Odpowiedź!
2010-02-27T18:51:10+01:00
6+(-4)+(-10)=6-4-10=2-10=-8
-4-(-9)-3=-4+9-3=5-3=2
-16+7-28=9-28=19
4,3-7,4+1,1=-3,1+1,1=-2
(-6,2)+1,6-(-2,3)=-4,6+2,3=-2,3
7,8-5,4-12,1=2,4-12,1=-9,7
1 ⅓+²/₉+⅙= 1 ⁶/₁₈ + ⁴/₁₈ + ³/₁₈ = 1 ¹³/₁₈
1 ⅛ -2 ¼ -(-½)= 1 ¹/₈ - 2 ²/₈ + ⁴/₈ = - 1⅛+⁴/₈ = -⅝
1 5 1